Incarnation: the person and life of Christ - Torrance, Thomas F. (Paternoster, 2008)
Author's foreword -- Preface / by Thomas S. Torrance -- Editor's foreword -- Synopsis -- Editor's introduction -- Introduction to christology -- The Incarnation -- The once and for all union of God and man -- The continuous union in the life of Jesus -- The mystery of Christ -- The hypostatic union -- The kingdom of Christ and evil -- Addendum: Eschatology